THE IMPACT OF BANK SIZE, RETURN ON EQUITY AND CAPITAL ADEQUACY RATIO ON NON PERFORMING LOANS - Risky Fitriany; Achmad Fadjar (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to examine the effects of Bank Size, Return on Equity (ROE), and Capital Adequacy Ratio (CAR) on Non-Performing Loans (NPL) in conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period. NPL is one of the key indicators used to assess loan quality and the level of credit risk faced by banks. A high NPL ratio may weaken banking stability, reduce profitability, and undermine public confidence in the banking sector. Therefore, identifying the determinants of NPL is essential for maintaining sound banking performance and financial stability. The independent variables employed in this study are Bank Size, Return on Equity (ROE), and Capital Adequacy Ratio (CAR), while NPL serves as the dependent variable. This research adopts a quantitative approach using secondary data obtained from the annual financial statements of conventional banks for the period 2021–2025. The data were measured using a ratio scale, and the sample was selected through a purposive sampling technique. A total of 42 conventional banking companies listed on the Indonesia Stock Exchange were included in the study. Panel data regression analysis was used EViews 13 software. The most appropriate estimation model was determined through the Chow test, Hausman test, and Lagrange Multiplier test. The findings reveal that Bank Size, ROE, and CAR also significantly affects NPL. These results suggest that bank size, Return on Equity (ROE), and and Capital Adequacy Ratio (CAR) are important factors influencing credit quality and should be carefully managed to control banking credit risk.